Molecular Modeling and Multiscaling Issues for Electronic Material Applications Volume 2 - Wymyslowski, Artur.; Wymyslowski, Artur.; Iwamoto, Nancy.; Iwamoto, Nancy.; Yuen, Matthew.; Yuen, Matthew.; Fan, Haibo.; Fan, Haibo. (Springer International Publishing : Imprint: Springer, 2015)
This book offers readers a snapshot of the progression of molecular modeling in the electronics industry and how molecular modeling is currently being used to understand materials to solve relevant issues in this field. The reader is introduced to the evolving role of molecular modeling, especially seen from the perspective of the IEEE community and modeling in electronics. This book also covers the aspects of molecular modeling needed to understand the relationship between structures and mechanical performance of materials. The authors also discuss the transitional topic of multiscale modeling and recent developments on the atomistic scale and current attempts to reach the submicron scale, as well as the role that quantum mechanics can play in performance prediction. This book also: Discusses multiscale modeling of materials at the mesoscale Highlights current state-of-the-art, novel research topics and achievements in the area of molecular modelling and multiscaling problems of electronic materials and their applications as well as atomistic modeling of mechanical properties Provides practical examples for engineers interested in molecular modeling using simulations drawn from electronic packaging, dielectric materials, and thermal and mechanical properties.